PTU-003 Filgotinib decreases inflammatory markers associated with endoscopic improvement in moderate to severely active crohn's disease. (8th June 2018) - Keshav, Satish; Roblin, X; D'Haens, G; Galien, R; Goyal, L; Li, W; Mirza, A; Serone, A; Tasset, C; Van der Aa, A; Woo, J; Vermeire, S
Abstract : Introduction: Filgotinib (FIL) is a JAK1-selective inhibitor currently in Phase III development for the treatment of ulcerative colitis and Crohn's disease (CD). In a Phase II study in patients with moderately to severely active CD (FITZROY, ClinicalTrial.gov ID#NCT02048618 ), 10 weeks of treatment with FIL 200 mg once daily demonstrated significantly higher clinical remission rates compared with placebo. Here, we report treatment-induced changes in serum cytokines, C-reactive protein (CRP) and faecal calprotectin (FC) and investigation of the association of these biomarkers with endoscopic changes. Methods: Serum samples were acquired at baseline (BL), and Weeks 2, 4, and 10 and stool samples collected at BL and Week 10. Serum cytokines were measured by chemiluminescence, CRP by immunoturbidimetry and FC by Calprest ® . Percent change of biomarkers from BL at post-treatment visits were compared between placebo (PBO) (n=44) and FIL-treated (n=128) patients using an ANCOVA model adjusting for BL biomarker levels and stratification factors (steroid use, prior anti-TNF exposure and BL CRP). Association of% change in biomarkers with Week 10 endoscopic response (≥50% decrease from BL in SES-CD score) was assessed by AUROC. Results: Biomarker levels at BL were comparable between PBO and FIL treatment groups, except IL-17A and VEGF-A which were higher in PBO (medians at 3.2 and 547.2 pg/ml) vs. FIL group (1.3 and 389.6 pg/ml, p<0.05). FIL treatment induced reductions in FC (median% change of −30% to −35%), serum IL-6 (−11% to −20%) and serum VEGF-A (−8% to −12%) were observed at all time points. Decline in FC, CRP and VEGF-A in FIL-treated patients was observed at Week 2 and was significant compared with PBO-treated patients (p<0.05). No significant change was observed for IL-10, IFN-g, and IL-8. No significant changes were observed in PBO-treated patients. In FIL-treated patients, a significant association was observed between the decrease in both systemic (serum CRP and IL-6) and mucosal (FC) biomarkers and endoscopic response. Conclusions: Filgotinib treatment led to an early reduction in markers of systemic and mucosal inflammation that correlated significantly with endoscopic response.